HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP DENGAN PRAKTIK IBU DALAM PEMBERIAN MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI) DI MURNI TEGUH ROSIVA MEDAN - Hayati, Hayati; Tambunan, Dior Manta (Indonesian Trust Nursing Journal, 2025)
Breast milk complementary food is a type of food given in addition to breast milk, starting at the age of toddlers between 6 months and 24 months. In fact, there are still many mothers in the practice of providing Breast milk complementary food is not in accordance with the age of the baby so that they can growth problems. It might be related to woman’s knowledge and attitude factor. The purpose of this study was to determine the relationship between the level of knowledge and attitude with the breastfeeding woman practice in providing Breast milk complementary food. The research method is a quantitative study with a correlational study design using a cross-sectional approach. The sample in this study amounted to 52 respondents with purposive sampling technique. Data analysis used the Pearson test and Anova test. The result of this study with the Pearson test showed a relationship between Breastfeeding Woman’s knowledge and attitudes with breastfeeding woman practice in providing Breast milk complementary food as indicated by a p-value <0.05. The Anova test explains that there is a relationship between breastfeeding woman’s knowledge and attitudes with breastfeeding woman practice in providing Breast milk complementary food as indicated by p-value <0.05. It is recommended that nurses play an active role in providing education to breastfeeding woman’s and their families in the practice of providing complementary feeding, and further research to conduct research related to the provision of complementary feeding using motivation variables, family support, and support from health workers.